Leishmaniose visceral canina em Barão de Melgaço, Mato Grosso : sorologia e análise espacial - Dias, Álvaro Felipe de Lima Ruy (2016)
Visceral leishmaniasis is an important zoonosis in public health, with the domestic dog as the main reservoir of the disease in the urban environment. This study aimed to evaluate the prevalence and spatial distribution of canine visceral leishmaniasis (CVL), as well as factors associated with the disease in Barão de Melgaço. Tests used were recommended by the Ministry of Health of Brazil, the rapid immunochromatographic teste and immunosorbent assay to evaluate 402 serum samples from dogs of urban and rural area of the municipality. The address of the residences was plotted by census sector and spatial analysis was performed using the global and local Moran indices. Seventeen dogs reacted in both serological tests, with a prevalence of 4.2% in the municipality. A low correlation was found between the two serological tests (Kappa = 0.21). Hyperkeratosis and splenomegaly were identified as factors associated with CVL (p <0.05). Global Moral index was used to generate a choropleth map of LVC, noting weak correlation, but statistically significant effect on the rates of disease (I <0.5). Local Moran Index was used to generate clusters map, being identified census tracts with high, low and intermediate priority for control of LVC, finding only a high- priority sector, having this as a characteristic, the presence of urban and rural region its limits. The LVC is present in the city of Barão de Melgaço, with a prevalence of 4.2%, characterizing it as area with moderate and responsive transmission to human cases. The spatial analysis of data from the study in Barão de Melgaço allowed the visualization of the disease situation in the different sectors analyzed. The only census tract classified as high priority, comprises urban and rural areas of the municipality, this premise, the water cycle that occurs every year in the Pantanal, may predispose the spread of the disease in urban areas. Key-words: Dog, Epidemiology, Georeferencing,